Perestroika and the Collapse of the USSR. Some Reflections - Norbert Frejek (Історико-політичні проблеми сучасного світу)
This text offers some reflections related to perestroika and glasnost – two flagship projects of the era of Mikhail Sergeyevich Gorbachev – the last leader of the Soviet Communist Party. Not counting his two immediate predecessors, who were elected in old age, Gorbachev proved to be the shortest-reigning Soviet leader. His plans for reform were linked to economic stagnation and the crisis of the state. He is often regarded, especially in the post-Soviet area, as the main culprit (often alongside Yeltsin) for the collapse of the USSR and its loss of superpower status. This is not entirely true, however, as Gorbachev found a state that was badly managed, stagnant and with a deepening crisis of confidence among its citizens. His reforms only accelerated the process of erosion of state structures and the economy that had been going on for years. In addition to seeing the last years of the USSR in the key of the collapse, it should also be emphasized that many of the former republics broke out into independence. Especially Ukraine, the Baltic republics and Kazakhstan have definitively separated themselves from Russia in terms of the country-building project, its structures and its economy. The terms perestroika and glasnost have permanently entered the language of political science, but Gorbachev was much more popular in the West. In the former USSR, and especially in Russia, he was and is highly criticized. The author of the text recalls the thesis of the Polish philosopher and expert on Marxism, Leszek Kołakowski, that the USSR could only survive if governed in the style that Stalin did, i.e. in a dictatorial manner. Other ways of governing the country, including attempts at reform, proved to be the road leading to disintegration.